Trends in mortality and factors associated with mortality and morbidity amongst hospitalized low birth weigth infants at a tertiary level hospital in Cameroon, 2001-2005 - Wiyeh, Alison Beriliy (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.